Edukasi Interakktif SI PITA Melalui Media Powerpoint dan Puzzle di SMPN 28 Jakarta - Sada Rasmada; Mateus Bagas Nugroho Jati; Paramitha Wirdani Ningsih Marlina; Agnes Maharani Puji Wulandari; Aloysius Prima Cahya Miensugandhi; Damelya Patriksia Dampang (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: This community service program aimed to improve adolescents’ knowledge of balanced nutrition guidelines through an interactive educational program at SMPN 28 Jakarta. The identified problem was the low level of students' knowledge regarding the “Isi Piringku” concept, which may affect nutritional status and eating habits among adolescents. The method was conducted through three stages: preparation, implementation, and evaluation. The intervention consisted of nutrition education delivered using PowerPoint media, followed by a practical activity involving the arrangement of the Isi Piringku puzzle. The evaluation employed a pre-test and post-test design involving 30 seventh-grade students to assess changes in knowledge before and after intervention. Data were analyzed using the Wilcoxon test, which showed a significant difference between pre-test and post-test scores (p=0.003). The proportion of students with good knowledge increased from 6,7% to 26,7% after the intervention. Monitoring conducted three days after the education session indicated that some students had begun applying the “Isi Piringku” concept, although food availability at home remained a challenge. This study concludes that education using visual media and interactive practices is effective in improving adolescents' nutritional knowledge; however, support from families and schools is necessary to optimize sustainable behavioral changes. Keyword: adolescent knowledge; balanced nutrition education; community service Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan remaja mengenai pedoman gizi seimbang melalui program edukasi interaktif. Permasalahan yang dihadapi adalah masih rendahnya tingkat pengetahuan siswa tentang konsep Isi Piringku, yang berpotensi memengaruhi status gizi dan kebiasaan makan remaja. Metode kegiatan dilakukan melalui tahapan persiapan, pelaksanaan, dan evaluasi. Intervensi berupa edukasi gizi menggunakan media PowerPoint dan praktik penyusunan puzzle Isi Piringku. Evaluasi dilakukan menggunakan pre-test dan post-test pada 30 siswa kelas VII. Analisis menggunakan uji Wilcoxon menunjukkan perbedaan signifikan antara nilai pre-test dan post-test (p=0,003). Persentase pengetahuan kategori baik meningkat dari 6,7% menjadi 26,7% setelah intervensi. Monitoring tiga hari pascaedukasi menunjukkan sebagian siswa mulai menerapkan konsep isi piringku, meskipun masih terdapat hambatan pada ketersediaan pangan di rumah. Kegiatan ini menyimpulkan bahwa edukasi menggunakan media visual dan praktik interaktif efektif dalam meningkatkan pengetahuan gizi remaja, namun diperlukan dukungan keluarga dan sekolah untuk optimalisasi perubahan perilaku Kata kunci: edukasi gizi; isi piringku; pengabdian masyarakat